Research and Experiment on Self-Decoupling Method for Non-Intrusive Measurement of Transmission Line Voltage - Jiaquan Yang; Yang Yang; Xudong Zhang; Xiao Du; Qingyang Xie; Jingang Wang; Wei Zhang (IEEE Access, 2023)
Non-invasive voltage measurement of transmission lines plays an important role in the process of power system digitization. Aiming at the phase to phase coupling effect of the field source structure of the transmission line, the paper proposed a self-decoupling voltage measurement method based on the field source structure parameters of the measuring point, to achieve the accurate measurement of three-phase voltage by a single sensor. Voltage measurement is achieved at the measuring point of the sensor by utilizing a three-dimensional electric field induction probe. The principle of voltage self-decoupling measurement is introduced in this paper. The measurement model of voltage self-decoupling is analyzed. Simulation calculations are then performed to calculate and adjust the coefficient of the self-decoupling matrix. Finally, the voltage measurement and decoupling effect of this method are verified using a three-phase horizontal distribution transmission line as an example. The results show that the voltage measurement error under steady-state and transient conditions is less than 2.8% and 2.2% respectively. This method can be used for voltage measurement of transmission lines.